2009
DOI: 10.1146/annurev.polisci.12.060107.154208
|View full text |Cite
|
Sign up to set email alerts
|

Experiments on Racial Priming in Political Campaigns

Abstract: Since the first half of the twentieth century, whites have become much more accepting of the principle of racial equality even as they have continued to endorse negative racial stereotypes about African-Americans. Some scholars argue that this ambivalence has been exploited by contemporary political elites who have learned to fashion subtle racial appeals that activate these latent attitudes without appearing to violate widely held norms of racial equality. This strategy has been dubbed racial priming. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 10 publications
0
54
0
Order By: Relevance
“…Taken together, these results provide further support for previous research, which has shown heterogeneity in responses to racial priming across different racial groups. The inconsistent pattern of effects for the nonwhite subjects in the studies also raises questions as to whether members of less-frequently studied racial groups (such as Asians and Hispanics) are in fact relatively unaffected by, or in fact themselves respond differently to subconscious racial priming, a notion posited but largely untested thus far in work on race priming (Hutchings and Jardina 2009). Unfortunately this premise cannot be tested directly by this study due to limited numbers of respondents in these groups in the sample; however, the apparent heterogeneity in priming effects across racial groups would seem to suggest an area ripe for future work.…”
Section: Resultsmentioning
confidence: 98%
“…Taken together, these results provide further support for previous research, which has shown heterogeneity in responses to racial priming across different racial groups. The inconsistent pattern of effects for the nonwhite subjects in the studies also raises questions as to whether members of less-frequently studied racial groups (such as Asians and Hispanics) are in fact relatively unaffected by, or in fact themselves respond differently to subconscious racial priming, a notion posited but largely untested thus far in work on race priming (Hutchings and Jardina 2009). Unfortunately this premise cannot be tested directly by this study due to limited numbers of respondents in these groups in the sample; however, the apparent heterogeneity in priming effects across racial groups would seem to suggest an area ripe for future work.…”
Section: Resultsmentioning
confidence: 98%
“…8 4 The research paradigm here grows out of Mendelberg 2001. Mendelberg and others found that pairing otherwise neutral descriptions of candidates or issues with images confirming racist stereotypes tends to make belief in racist stereotypes a better predictor of that individual's attitudes towards social policies favoring African Americans and towards the politicians described than when paired with neutral images (Valentino et al 2002), counter-stereotypical images (Mendelberg 2001, Valentino et al 2002, and when the the description of the issue involves explicit endorsement of such racist stereotypes (Mendelberg 2001; see also Hutchings & Jardina 2009, Mendelberg 2008 for more results). 5 This measure of racial resentment follows Kinder & Sanders 1996, which is the standard way of unobtrusively measuring the degree of racial bias in an individual.…”
Section: Fixing Ideas: Some Effects Of Code Wordsmentioning
confidence: 99%
“…Similarly, participants have been found to be more likely to categorize ambiguously raced faces as Black when they are dressed in low-status attire (Freeman, Penner, Saperstein, Scheutz, & Ambady, 2011). And, simply using terms such as "welfare" or priming race in the context of welfare is sufficient to create an association between one's racial stereotypes and attitudes and one's policy preferences (Gilens, 1999;Mendelberg, 2001; for a review see Hutchings & Jardina, 2009). Thus, even though racially prejudiced, lower SES White individuals may benefit from welfare policies, they, along with their higher SES counterparts, may oppose these policies because they believe them to benefit racial minorities.…”
Section: Socioeconomic Status and Attitudes Toward Redistributionmentioning
confidence: 99%